Social support and mental health of young people in residential care : a qualitative study - Ferreira, Sofia (Colegio Oficial de Psicólogos de Madrid, 2020)
The literature suggests the positive role of social support in mental health in residential care. However, most of the studies are focused on psychopathology and fewer on well-being. Also, theoretically-oriented and multidimensional studies on social support are needed. To address these problems, a qualitative study was developed with 29 young people in residential care (76% males), aged from 12 to 19 years old. Data was collected with a semi-structured interview. Results showed young people identify meaningful sources of social support (peers, residential care, and family), considering them available and effective support providers. Social support was also identified as an enhancer of positive psychological functioning and as a buffer of psychological functioning problems. Future research should involve more systematic, multidimensional approaches, both in assessing social support and in mental health. Important implications are recognized for professionals in the justice system.